Bangladesh Country Environmental Analysis - World Bank (World Bank, Washington, DC, 2020)
The economic losses resulting from the environmental impacts considered in this report are equivalent to more than 4 percent o f Bangladesh's Gross Domestic Product. Among these impacts, three sources of environmental degradation stand out as currently receiving insufficient attention given their relative significance: (1) in door and urban air pollution, (2) the degradation o f water quality in Dhaka, and (3) the decline of capture fisheries. The economic losses associated with these three concerns alone may amount to more than 2.7 percent of GDP. The report proposes a set of actions in each o f these areas, and also identifies a series of measures that could be taken to strengthen environmental governance, which forms an overarching constraint to improved environmental management across all issues. While the report estimates the economic losses associated with the environmental impacts considered, it does not provide a benefit-cost or cost-effectiveness analysis of the proposed mitigating actions. It will be important to examine the costs of the proposed actions in more detail as an element of the follow-up work in each o f the priority areas.